Compreensão leitora do gênero multimodal tira: uma análise de atividades de leitura propostas por livros didáticos de língua portuguesa do ensino médio - Silva, Izabelle Fernandes da (2019)
The texts that circulate today are made in many genres and increasingly employ nonverbal elements (images, colors, shapes, sounds, gestures, etc.) that integrate and combine with verbal elements (words), which characterize them as multimodal genres. These genres combine at least two semioses (modes of meaning) and therefore require readers to understand that nonverbal elements do not fulfill a mere illustrative function, that they have a sense / informative load, which have communicative purpose and, being a constituent part of these texts, they are essential in the process of constructing their meanings, influencing their comprehension and the realization of their communicative purpose. Considering the new learning demands of students regarding the reading of multimodal / multisemiotic texts, we are concerned with how these texts are worked in the reading activities proposed for them. Thus, due to the remarkable presence of the textbook in Brazilian schools, we took as source for collecting the data analyzed by this research three textbooks of the first year of high school, each book in a collection approved by the National Textbook Program - PNLD. Considering also the characteristics and the pedagogical potentialities of the strips as a multimodal discursive / textual genre, our objective is to verify which reading skills are developed by the activities proposed for this genre by the three selected books. In addition, we are interested in investigating whether these reading activities proposed for the strips include the processing of the nonverbal language that constitutes this genre and its integration with the verbal language that makes up these texts. Data analysis revealed that the semantic relationship established between the verbal and nonverbal languages that constitute the strips proposed by the three selected textbooks is complementary, pointing out that most of these texts have great potential for reading activities to address skills that include the textual processing of visual language and its integration with verbal language. As for the analysis of the reading activities proposed for the 21 selected strips, we emphasize that none of the three books promotes the development of critical analysis skills of the strips either in terms of textual structure, content or discourse. The data also reveal that, in the three textbooks, some reading skills are not addressed by the reading comprehension activities proposed for the selected strips, although some of these texts present material that favors the approach of these neglected skills. Although the three books propose activities that address reading skills that include visual language processing and its integration with verbal language, in general, their didactic treatment in reading activities does not favor the mobilization of reading skills to the specifics of this multimodal genre. Thus, these didactic materials limit reading teaching and learning and contribute to the multimodal literacy of high school students from Brazilian public schools. We hope that this work can contribute to reflections on the need for a reading education that promotes multiliteracy and a teaching-learning that favors the development of specific skills for reading the strips, but also of other multimodal genres.